2021
DOI: 10.1149/1945-7111/ac1e55
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study of Electrolyte Additives in Single Crystal and Bimodal LiNi0.8Mn0.1 Co0.1O2/Graphite Pouch Cells

Abstract: A few weight percent of electrolyte additives can dramatically improve Li-ion battery performance and lifetime. A systematic investigation of a series of electrolyte additive formulations was performed on bimodal (BM) and single crystal (SC) LiNi0.8Mn0.1Co0.1O2 (NMC811)/artificial graphite (AG) pouch cells. Long-term cycling tests at different temperatures (20 °C, 40 °C, and 55 °C) and different upper cutoff voltages (4.06 V and 4.20 V) were performed. These tests results were combined with advanced characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 44 publications
3
56
0
Order By: Relevance
“…For instance, a similar study to that presented here could be worth doing based on the recent publication on a battery using a positive electrode (NMC811), which is prone to intense reaction. [ 31 ] They are known to lead to CO 2 production. [ 64 ] Therefore, depending on the experimental conditions, the choice of the marker of the degradation in the radiation chemistry experiments, may be different.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a similar study to that presented here could be worth doing based on the recent publication on a battery using a positive electrode (NMC811), which is prone to intense reaction. [ 31 ] They are known to lead to CO 2 production. [ 64 ] Therefore, depending on the experimental conditions, the choice of the marker of the degradation in the radiation chemistry experiments, may be different.…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ] Over the years, the same group has continuously been adding more data on other systems till recently and based on similar protocols to that developed in 2014. [ 31 ] In the work performed in 2014, [ 28 ] the relationship between the nature and amount of several additives and the electrochemical performance of the formulation was determined by high precision coulometry and impedance spectroscopy in LiCoO 2 /graphite pouch cells. The authors ranked additives and identified the best ones based on a marker representing the degradation of the battery, i.e., the charge slippage.…”
Section: Introductionmentioning
confidence: 99%
“…[168] Archimedes' principle has been used to devise a method of monitoring cell volume during operation and provides a more accurate representation of the amount of gas evolution. [169,170] Although these methods give information about the extent of gassing, they do not give information about the composition of the gases. Gas chromatography and mass spectrometry are techniques being developed to identify these gases.…”
Section: Electrolyte Filling and Wettingmentioning
confidence: 99%
“…However, this inaccurately assumes that the expansion is uniform throughout the cell [168] . Archimedes′ principle has been used to devise a method of monitoring cell volume during operation and provides a more accurate representation of the amount of gas evolution [169,170] . Although these methods give information about the extent of gassing, they do not give information about the composition of the gases.…”
Section: Data Specificationsmentioning
confidence: 99%
“…To mitigate the above issues, several strategies have been attempted: doping, surface modification, surface modification via intentional electrolyte additive decomposition, process refinement, , TM concentration gradient, core–shell structures, grain boundary tailoring, and single-crystalline morphology. , Individually, these modifications fail to generate nickel-rich cathode materials with optimum cycle life retention and air stability for commercial use. Particle cracking may still occur with high-voltage cycling, slowly degrading performance, and air instability allows residual lithium compounds to form during material synthesis and electrode production.…”
Section: Introductionmentioning
confidence: 99%